CLIMATE CHANGE IN ENVIRONMENTAL IMPACTS ASSESSMENT - CARVALHO, Alina Silva de; ROSA, Claudio Damião; SILVA, Elaine Aparecida da; LINS, Ittana de Oliveira; ALMEIDA NETO, José Adolfo de (Editora IOLE, 2024)
The Environmental Impact Assessment (AIA) is a procedural instrument that examines the social, economic and environmental consequences of the implementation, operation and deactivation of a project, whether beneficial or adverse. EIA is essential in decision-making in environmental licensing for projects with the potential to cause significant environmental impacts. Although there is a dominant consensus in the scientific community that climate change resulting from anthropogenic activities constitutes a threat to life on Earth, there is still no consensus on how to consider potential impacts on climate within EIA. Through this systematic review, the proposals that have been discussed in the international literature for considering potential impacts on climate in studies within the EIA were identified and described. Published studies with proposals for quantifying and incorporating emissions that contribute to climate change were included. From a geographic point of view, the 21 studies included in this review covered all continents, with the exception of Antarctica. In South America, studies were found in Argentina and Bolivia, with no studies identified in Brazil. As a result, among the proposals presented, the tool that appears most frequently is the Life Cycle Assessment (LCA), discussed in 71% of the studies. It is concluded that EIA is fundamental for mitigating impacts on the environment, and it is imperative that its deficiencies are minimized and that a standard of analysis is established, considering impacts related to climate change.